2009
DOI: 10.1101/gad.1863009
|View full text |Cite
|
Sign up to set email alerts
|

Nearby inverted repeats fuse to generate acentric and dicentric palindromic chromosomes by a replication template exchange mechanism

Abstract: Gene amplification plays important roles in the progression of cancer and contributes to acquired drug resistance during treatment. Amplification can initiate via dicentric palindromic chromosome production and subsequent breakage-fusion-bridge cycles. Here we show that, in fission yeast, acentric and dicentric palindromic chromosomes form by homologous recombination protein-dependent fusion of nearby inverted repeats, and that these fusions occur frequently when replication forks arrest within the inverted re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
185
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(193 citation statements)
references
References 45 publications
7
185
1
Order By: Relevance
“…Palindromes-a specific type of inverted repeat separated by only very few base pairs-are poorly tolerated in Escherichia coli cells and are underrepresented in the S. cerevisiae and human genomes (Lobachev et al 2000;Stenger et al 2001), presumably due to their tendency to form hairpin and cruciform structures (Lobachev et al 2002;Lemoine et al 2005), which could be recognized and cleaved by a nuclease (Leach and Stahl 1983) or could affect or slow down DNA replication (Ahmed and Podemski 1998). Studies in budding yeast have shown that palindromes can rearrange to form acentric or dicentric chromosomes (Narayanan et al 2006;Voineagu et al 2008), a finding confirmed in fission yeast by a recent study (Mizuno et al 2009). Acentric and dicentric chromosomes are unstable chromosome intermediates: Acentric palindromic chromosomes have been proposed to be precursors for extrachromosomal elements.…”
Section: Inverted Repeats Palindromes and Dicentric Chromosome Formsupporting
confidence: 56%
See 2 more Smart Citations
“…Palindromes-a specific type of inverted repeat separated by only very few base pairs-are poorly tolerated in Escherichia coli cells and are underrepresented in the S. cerevisiae and human genomes (Lobachev et al 2000;Stenger et al 2001), presumably due to their tendency to form hairpin and cruciform structures (Lobachev et al 2002;Lemoine et al 2005), which could be recognized and cleaved by a nuclease (Leach and Stahl 1983) or could affect or slow down DNA replication (Ahmed and Podemski 1998). Studies in budding yeast have shown that palindromes can rearrange to form acentric or dicentric chromosomes (Narayanan et al 2006;Voineagu et al 2008), a finding confirmed in fission yeast by a recent study (Mizuno et al 2009). Acentric and dicentric chromosomes are unstable chromosome intermediates: Acentric palindromic chromosomes have been proposed to be precursors for extrachromosomal elements.…”
Section: Inverted Repeats Palindromes and Dicentric Chromosome Formsupporting
confidence: 56%
“…Since nearby inverted repeats separated by a few kilobases of DNA are unlikely to form cruciform structures as do palindromes, it is most probable that the mechanisms leading to formation of dicentric and acentric chromosomes in these situations are also different. The recent studies by Paek et al (2009) and Mizuno et al (2009) characterized the factors influencing the formation of acentric and dicentric chromosome intermediates at nearby inverted repeats or palindromic loci in budding and fission yeast, respectively.…”
Section: Inverted Repeats Palindromes and Dicentric Chromosome Formmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, stalled forks have recently been shown to produce DSB-independent fusions of nearby inverted-repeats, which lead to the formation of palindromic chromosomes (Mizuno et al 2009;Paek et al 2009). The mechanisms by which these fusions take place remain a subject of debate, and three distinct possibilities have been proposed: faulty template switching, tandem inversion duplications, and replication U-turns (Mizuno et al 2009(Mizuno et al , 2013Paek et al 2009;Kugelberg et al 2010;Seier et al 2012).…”
mentioning
confidence: 99%
“…Replication fork stalling or blockage at both accidental and programmed DNA-protein barriers can induce recombination events, which in turn can result in genomic rearrangements that can be deleterious to the cell (Ahn et al 2005;Lambert et al 2005Lambert et al , 2010Mizuno et al 2009). RFBs can also lead to stretches of unreplicated DNA that persist into mitosis, causing anaphase bridge formation and, ultimately, chromosome breakage and genome instability (Jacome and Fernandez-Capetillo 2011;Sofueva et al 2011).…”
mentioning
confidence: 99%